THE EFFECTS OF SUPPLY CHAIN MANAGEMENT PRACTICES ON TECHNOLOGICAL INNOVATION: A CASE OF MANUFACTURING SECTOR OF PAKISTAN - SYED ATIF ALI WARSI; DR. MUHAMMAD ASIM; SALMAN MANZOOR (CenRaPS Journal of Social Sciences, 2020)
The purpose of the study is to examine the relationship between supply chain management practices (SCMP) on technological innovation in the manufacturing sector organizations of Pakistan. The supply chain management practices (SCMP) include in this study are strategic supplier partnership, information sharing, information quality, postponement and internal lean practices while technological innovation being the dependent variable. The target population for this study has been selected as the manufacturing sector in Pakistan. The study has collected 200 responses from the supply chain professionals of manufacturing firms of Karachi, Pakistan. For analysis of data, partial least square structural equation modelling (PLS-SEM) named Smart PLS version 3.2.8 has been used. The finding of the study showed that supply chain management practices have a positive impact on technological innovation. The postponement has the highest impact and positive relation with technological innovation, then strategic supplier partnership was found to a positive and significant impact on technological innovation, while information quality has lower impact and positive relationship with technological innovation. The study suggests that manufacturing firms should implement proper supply chain management practices for making their product and process innovations. The paper will provide insights to the manufacturing firm how these supply chain management practices help in technological innovation.